Asset Bubbles, Pay as You Go Systems and Dynamic Efficiency - Lang, Günther (2019)
This paper deals with the role of bubbles, having the same meaning as Ponzi games, for implementing efficient growth paths in a closed economy overlapping generations model. It is shown that the well-known arbitrage condition for bubbles, namely that they must yield the same return in equilibrium as real assets, is generically neither necessary nor sufficient for a Pareto-improvement compared to a perfect-foresight equilibrium without bubbles. A consequence of this fact is that bubbles, or Ponzi games, are not Pareto-improving generically, and therefore, it can be irrational for agents to be on the demand side on the market for bubbles, although a bubbly equilibrium could exist.